Construct validity of the simplified Chinese version of the instrument ‘Picture My Participation’ - Linjun Shi; Mats Granlund; Yue Zhao; Karina Huus (Scandinavian Journal of Occupational Therapy)
Background Preliminary evidence of the content validity of the simplified Chinese version of ‘Picture My Participation’ (PMP-C; Simplified) items and reliability of the subscale attendance for the effectiveness of the use with children and youth in mainland China has been collected. However, evidence of construct validity for the instrument is not yet available.Aim To explore the construct validity of the attendance scale in PMP-C (Simplified).Methods A cross-sectional study using convenience sampling was conducted using PMP-C (Simplified) with a picture-supported interview for 290 children and youths aged 5–21 with and without ID in urban and rural areas of mainland China. Exploratory factor analysis (EFA) was performed using the principal component analysis (PCA) to analyse the resulting data.Results The EFA extracted five factors with eigenvalues greater than one and the cumulative contribution rate of factors accounted for 51.62% of the variance. All items had factor loadings above 0.50. The five subcomponents included: organised activities, social activities, taking care of others, family life activities and personal care and development activities.Conclusion The results of the factor analysis support the construct validity of the PMP-C (Simplified) attendance scale. It provides further psychometric evidence that PMP-C (Simplified) is a sound measure to assess participation for children and youths in mainland China.